VALORAÇÃO DE ATIVOS E MULTAS AMBIENTAIS: ANÁLISE SIMULADA DE EMPREENDIMENTOS HOTELEIROS EM ÁREAS PROTEGIDAS - Paim, Wilson Moisés (2014)
The disorderly urban development and a lack of an efficient public policy have prompted to a diversification of management to natural resources, mainly when are referring to water system and sanitations. The regulatory framework excised in 80 s decade established the public policy for the natural environment, which also brought new advance topics about that, triggering a numbers of actions that turned not only for bureaucratic structure and prevention, but also for solutions to the degradation and natural resources depletion. With the advent of the specific watershed source protection laws and the São Paulo State law number 13.579/09, that cares about Billings reserve area, it is notable an advance related to management issues of development and protection of the characteristics of its location. The government used practices of the law against environmental crimes as some public policy tools tactics to contain actions refers to the environment damaged. The objective of this research, is to analyze some possible discrepancies between the financial penalties applied when occurs environmental infractions and the Models of environmental evaluation assets, to affect a simulation of deploying a hotel within protected areas and recovery watershed source at São Bernardo County located in São Paulo State. The development of this research it was based on Modified Replacement Cost (MRC) to dimension the possible impacts brought from the Enterprise Lodge Inn and its respective economic values. After, the environment impacts were related to county laws to determined values with possible fines applied to the damage caused by those companies. Among the results raised, it was verify a significant discrepancy between economic valuation and the fines applicable, which means the impacts of fines applied against impermeability of soil and groundwater contamination becomes respectively with the different total amounts of R$ 804.922,78 and R$ 453.333,33. In the beginning of the methodology used in this research, it could notice that the fines applied in cases of damage to the environment sometimes doesnt achieve the objective of the protection, which is to inhibit the action of the offender, because the real economic cost doesnt measure the value of the penalty by the time is applied